An historical study of channel change in the Bell river, north eastern Cape - Dollar, Evan S J (Rhodes University, Faculty of Science, Department of Geography, 1993)
Channel instability has occurred in the Bell river, north eastern Cape, in the form of meander cutoffs, incipient meander cutoffs, channel straightening and general channel instability. Recent cutoffs occurred in 1974 and 1988. The study examines the spatial and temporal controls of channel form and pattern in the Bell river in order to assess the causes of channel instability. From the 17 km surveyed stretch, it was found that the main spatial controls of channel form were riparian vegetation density and channel bed material. Discharge as estimated in the field was not the main controlling variable of channel form. Two distinct groups of stream beds were identified from the survey; an upper gravel-bed stream and a lower sand-bed stream. These sites displayed distinct form ratios, channel gradients and bed material characteristics. The incidences of major channel instability were identified as being the transitional zone between the two reaches. Examination of temporal controls of channel form included climatic trend analysis and catchment sediment production analysis. Rainfall analysis indicated that no long term progressive trends in the annual or seasonal data existed. Distinct wet and dry cycles occur with peaks every 16 to 19 years. Wet cycles are the result of an increase in the frequency of daily events rather than in the magnitude of events. Flow record analysis demonstrated the relationship between regional discharge and upper catchment rainfall. Coincidence of peak flows and channel straightening were also noted. Soil erosion surveys showed that erosion had increased in the catchment and that accelerated erosion were probably the result of overstocking and poor veld management. It was concluded that channel changes in the Bell river are possibly the result of anthropogenic influence in catchment and channel processes. Increased sediment production to the channel resulted in channel aggradation with attendant instability. The plantation of riparian vegetation led to perimeter stability in the short term at flows less than bankfull discharge, but served to reduce cross-sectional area in the long term, thereby increasing the potential for flooding, meander cutoffs and channel change
Keywords: River channels -- South Africa -- Eastern Cape; Sedimentation and deposition -- South Africa -- Eastern Cape; Bell river